The protection of historical-artistic heritage during the Second Spanish Republic: Analysis of legal documentation - Nebreda Martín, Lara (Revista General de Información y Documentación, 2018)
The Second Spanish Republic was a drastic political change regarding the Bourbon Restoration, characterize by some legal provisions directed to regulate different aspects related to art, archaeology, history and culture in general. In this article we analyze the legislation relative to the conservation and protection of the historical-artistic heritage promulgated since the Second Republic until the outbreak of the Civil War (April 14, 1931 - July 17, 1936). Special attention is paid to the Law 13 of May 1933 and to the Decree of April 16, 1936, whereby the Regulation for the implementation of the above-mentioned law was approved. It also focuses on documentary aspects, such as the preparation of catalogues and inventories, and the application of photographic documentation as measures to preserve the Spanish cultural heritage.